Human Coronavirus NL63 Molecular Epidemiology and Evolutionary Patterns in Rural Coastal Kenya - Kiyuka, Patience K (J Infect Dis, 2018)
BACKGROUND: Human coronavirus NL63 (HCoV-NL63) is a globally endemic pathogen causing mild and severe respiratory tract infections with reinfections occurring repeatedly throughout a lifetime. METHODS: Nasal samples were collected in coastal Kenya through community-based and hospital-based surveillance. HCoV-NL63 was detected with multiplex real-time reverse transcription PCR, and positive samples were targeted for nucleotide sequencing of the spike (S) protein. Additionally, paired samples from 25 individuals with evidence of repeat HCoV-NL63 infection were selected for whole-genome virus sequencing. RESULTS: HCoV-NL63 was detected in 1.3% (75/5573) of child pneumonia admissions. Two HCoV-NL63 genotypes circulated in Kilifi between 2008 and 2014. Full genome sequences formed a monophyletic clade closely related to contemporary HCoV-NL63 from other global locations. An unexpected pattern of repeat infections was observed with some individuals showing higher viral titers during their second infection. Similar patterns for 2 other endemic coronaviruses, HCoV-229E and HCoV-OC43, were observed. Repeat infections by HCoV-NL63 were not accompanied by detectable genotype switching. CONCLUSIONS: In this coastal Kenya setting, HCoV-NL63 exhibited low prevalence in hospital pediatric pneumonia admissions. Clade persistence with low genetic diversity suggest limited immune selection, and absence of detectable clade switching in reinfections indicates initial exposure was insufficient to elicit a protective immune response.